EP300 promotes bladder cancer cell migration through SNAI2 - Qing Zhang; Chongjie He; Yingzhou Hong; Tao Huang; Shuangsheng Deng; Cheng Peng; Haifeng Wang; Chunming Guo (PLoS ONE, 2026)
EP300, a frequently mutated transcriptional coactivator in bladder cancer, has been demonstrated to positively correlate with malignancy in various cancers. Highly aggressive bladder cancers are often associated with muscle-invasive progression, a process closely linked to the epithelial-mesenchymal transition (EMT) capability of bladder cancer. Here, we performed immunohistochemical staining on bladder cancer tissues and adjacent normal tissues obtained from radical cystectomy to validate the positive association between EP300 and bladder cancer malignancy. We observed that A485, a small-molecule inhibitor of EP300, significantly inhibited cell migration in multiple bladder cancer cell lines (SW780, T24, RT4 and 5637) both in scratch wound healing and Transwell assays. Additionally, take the advantage of organoid-3D culture system, A485 disrupted the formation of inter-organoids connecting tubular structures in T24 cell line, while A485 also disrupted the organoid migration from matrix out-toward the non-matrix region both in SW780 and 5637 cell lines. In in vivo experiment, A485 showed a trend toward inhibiting BBN-induced bladder cancer invasion in mice. Bulk RNAseq analysis revealed that A485 commonly downregulated SNAI2-related signaling pathways across multiple bladder cancer cell lines. Furthermore, western blotting confirmed that A485 significantly reduced the global level of acetylation of histone H3 at lysine 27 (H3K27ac) as well as SNAI2 expression in T24 and SW780 cell lines. Indeed, overexpression of SNAI2 enhanced the migratory capacity of bladder cancer cells via Transwell assay. Collectively, our findings demonstrate that EP300 promoted bladder cancer cell migration via up-regulating SNAI2, targeting EP300 could be a potential therapeutic strategy to inhibit the process of bladder cancer invasion.